Предмет: Математика,
автор: алина555алина
1)Преобразуйте в многочлен стандартного вида
а) (а-4b)(a+4b) б) 5а(а+3)-(а-3)^2
Ответы
Автор ответа:
0
a) (a-4b)(a+4b)=a^2+4ab-4ab-16b^2=a^2-16b^2
b) 5a(a+b)-(a-3)^2=5a^2+5ab-(a^2-6a+9)=5a^2+5ab-a^2+6a-9=4a^2+5ab+6a-9
b) 5a(a+b)-(a-3)^2=5a^2+5ab-(a^2-6a+9)=5a^2+5ab-a^2+6a-9=4a^2+5ab+6a-9
Похожие вопросы
Предмет: Литература,
автор: Playkayt
Предмет: Алгебра,
автор: yangjeoning2002
Предмет: Математика,
автор: shikouwulolpip
Предмет: История,
автор: shmetatanya
Предмет: Физика,
автор: Аноним